Long-term clinical comparison of three different femoral stems in Total Hip Arthroplasty with femoral shortening in patients with high-riding hips - Kutalmis Albayrak; Yakup Alpay; Ozgur Ismail Turk; Muhammed Mert; Deniz Akbulut; Akif Albayrak (Journal of Orthopaedic Surgery and Research)
Abstract Background Developmental hip dysplasia is a common cause of hip arthrosis in young adults, necessitating total hip arthroplasty (THA) for improved function and pain relief. In cases of high-riding hips, transverse femoral shortening osteotomy is often required to facilitate reduction and prevent neurovascular complications. However, the choice of femoral stem in such cases remains controversial due to variations in design and osteoconductive properties. This study aimed to compare the clinical and radiological outcomes of three different femoral stems used in THA with transverse femoral shortening osteotomy. Methods A retrospective cohort study was conducted on 107 patients who underwent THA with transverse femoral shortening osteotomy between 2004 and 2014. Patients were divided into three groups based on the femoral stem used: Group 1 (Summit Tapered Stem (Depuy®) (n = 39), Group 2 (SL-PLUS Rectangular Stem (Smith & Nephew®) (n = 31), and Group 3 (Wagner Cone Prosthesis (Zimmer®) (n = 37). Clinical outcomes were assessed using the Harris Hip Score (HHS), and radiological evaluations included osteointegration and union rates. One-way ANOVA was used to compare continuous variables among groups, and post-hoc Tukey’s HSD test was applied for pairwise comparisons. Kaplan-Meier survival analysis was performed to evaluate implant survivorship. Results The mean preoperative HHS significantly improved from 42.7 ± 6.7 to 84.6 ± 11.5 postoperatively (p < 0.001). Group 3 had significantly higher final HHS compared to Group 1 (p = 0.0002), while no significant differences were observed between Group 1 and Group 2 (p = 0.1947) or Group 2 and Group 3 (p = 0.0723). The overall 10-year survival rate was 87.8%, with Group 3 demonstrating the highest survivorship (91%) and Group 2 the lowest (83%). Intraoperative femoral fissure or fracture rates were significantly higher in Group 1 compared to Group 3 (p = 0.0006), and with a significantly increased need for additional plating in Group 1 (p = 0.0031). Conclusions This study suggests that cylindrical fully porous-coated femoral stems (Wagner Cone Prosthesis) provide better clinical outcomes, fewer intraoperative complications, and higher long-term survival rates compared to tapered and rectangular stems in THA with femoral shortening osteotomy. These findings highlight the importance of implant selection in optimizing patient outcomes. Clinical trial number Not applicable.